2013
DOI: 10.1073/pnas.1303890110
|View full text |Cite
|
Sign up to set email alerts
|

Protein–DNA complexes are the primary sources of replication fork pausing in Escherichia coli

Abstract: Replication fork pausing drives genome instability, because any loss of paused replisome activity creates a requirement for reloading of the replication machinery, a potentially mutagenic process. Despite this importance, the relative contributions to fork pausing of different replicative barriers remain unknown. We show here that Deinococcus radiodurans RecD2 helicase inactivates Escherichia coli replisomes that are paused but still functional in vitro, preventing continued fork movement upon barrier removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 41 publications
3
106
0
Order By: Relevance
“…Recent biological data have suggested that protein-DNA complexes are the primary source of replication fork pausing in E. coli (46). Emerging evidence supports a model in which replication collisions are overcome by accessory helicases that assist the replisome to progress through protein-DNA blockades (32).…”
Section: Discussionmentioning
confidence: 96%
“…Recent biological data have suggested that protein-DNA complexes are the primary source of replication fork pausing in E. coli (46). Emerging evidence supports a model in which replication collisions are overcome by accessory helicases that assist the replisome to progress through protein-DNA blockades (32).…”
Section: Discussionmentioning
confidence: 96%
“…It was recently shown that D. radiodurans RecD2 causes collapsed E. coli replication forks to fail to reactivate in vitro and in vivo (64). Interestingly, D. radiodurans RecD2 overexpressed in E. coli was lethal to ⌬rep helicase mutants.…”
Section: Recd2 Limits Fork Stressmentioning
confidence: 99%
“…Consistent with RF pausing at protein-DNA complexes being a universal threat to genome stability, Escherichia coli also possesses accessory DNA helicases that act to clear protein-DNA barriers ahead of RFs 14 . Indeed, protein-DNA complexes are frequent sources of RF pausing in this organism 15 . Interestingly, E. coli also exhibits at least one example of programmed RF pausing, and this process is required to coordinate efficient DNA replication termination and chromosome segregation.…”
mentioning
confidence: 99%